Bellarmine and the «De Auxiliis» Controversy: About an Unpublished Manuscript on Middle Knowledge - Torrijos Castrillejo, David (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2022)
To commemorate the 400th anniversary of the death of St. Robert Bellarmine, this article pays attention to his significant contribution to the De Auxiliis controversy. The main milestones of his intervention are considered: Bellarmine’s internal censure of the Concordia by Molina made for Aquaviva, as well as some details of his relationship with Pope Clement VIII. He composed several opuscules on these topics, most of which have already been published. Here we transcribe an unpublished manuscript from the last years of De Auxiliis Congregations. It is a report written for Pope Paul V on the divine knowledge of conditioned futures. This question provides Bellarmine with another opportunity to criticize the doctrine of physical predetermination. According to the Jesuit cardinal, such a thesis was more dangerous a doctrine than the erroneous affirmations that even he could recognize in the Concordia by Molina.
Keywords: predetermination; divine providence; free will; grace; omniscience; Inquisition; theological anthropology